Flyway‐scale GPS tracking reveals migratory routes and key stopover and non‐breeding locations of lesser yellowlegs. Issue 11 (9th November 2022) - McDuffie, Laura A.; Christie, Katherine S.; Taylor, Audrey R.; Nol, Erica; Friis, Christian; Harwood, Christopher M.; Rausch, Jennie; Laliberte, Benoit; Gesmundo, Callie; Wright, James R.; Johnson, James A.
Abstract: Many populations of long‐distance migrant shorebirds are declining rapidly. Since the 1970s, the lesser yellowlegs ( Tringa flavipes ) has experienced a pronounced reduction in abundance of 63%. The potential causes of the species' decline are complex and interrelated. Understanding the timing of migration, seasonal routes, and important stopover and non‐breeding locations used by this species will aid in directing conservation planning to address potential threats. During 2018–2022, we tracked 118 adult lesser yellowlegs using GPS satellite tags deployed on birds from five breeding and two migratory stopover locations spanning the boreal forest of North America from Alaska to Eastern Canada. Our objectives were to identify migratory routes, quantify migratory connectivity, and describe key stopover and non‐breeding locations. We also evaluated predictors of southbound migratory departure date and migration distance. Individuals tagged in Alaska and Central Canada followed similar southbound migratory routes, stopping to refuel in the Prairie Pothole Region of North America, whereas birds tagged in Eastern Canada completed multi‐day transoceanic flights covering distances of >4000 km across the Atlantic between North and South America. Upon reaching their non‐breeding locations, lesser yellowlegs populations overlapped, resulting in weak migratory connectivity. Sex and population origin were significantly associated with the timing of migratory departure from breeding locations, and body mass at the time of GPS‐tag deployment was the best predictor of southbound migratory distance. Our findings suggest that lesser yellowlegs travel long distances and traverse numerous political boundaries each year, and breeding location likely has the greatest influence on migratory routes and therefore the threats birds experience during migration. Further, the species' dependence on wetlands in agricultural landscapes during migration and the non‐breeding period may make them vulnerable to threats related to agricultural practices, such as pesticide exposure. Abstract : Since the 1970s, the lesser yellowlegs ( Tringa flavipes ) has experienced a pronounced reduction in abundance of 63%. The potential causes of the species' decline are complex and interrelated and understanding the timing of migration and seasonal routes used by this species will aid in directing conservation planning to address potential threats. Our objectives were to identify migratory routes, quantify migratory connectivity and describe key stopover and non‐breeding locations.